Phase-field damage of laminated glass in explicit dynamics - Jaroslav Schmidt; Tomáš Janda (Acta Polytechnica CTU Proceedings)
Laminated glass is aesthetic but also functional modern material, which has spread from the automotive industry to the civil engineering in the form of design as well as structural elements. Proper design of this material requires understanding not only its intact phase, but also its post-breakage behavior. To describe crack initiation and propagation the phase field damage model seems to be suitable tool despite the fact that this approach requires a fine mesh to sufficiently interpolate sharp discontinuity. In this contribution we investigate possibilities of explicit phase field dynamic model with specific use on glass plates, especially applied for dynamic impact load. The dependence of the result on residual stiffness term is examined and incorrect crack speed is observed. Usability of phase-field model is still uncertain.